Kepatuhan Zakat Oleh Syarikat Tersenarai Awam Di Malaysia - Abdul Wahab, A.; Borhan, J. T. (Universiti Sains Islam Malaysia, 2024)
The main purpose of this study is to measure zakat compliance among Public Listed Companies (PLCs) in Malaysia. The study evaluates the zakatability status of shariah- compliant securities companies by Securities Commission's Shariah Advisory Council including main board and ACE Market. The information obtained from the latest annual report available and 811 annual reports were examined out of 817 syariah-compliant securities companies. Firstly, this study identifies companies with majority Muslim shareholders. Based on the largest shareholders reports, 118 companies are treated as owned by Muslim. Secondly, this study identifies zakat payment from the companies for 6 year period i.e. 2009 - 2014. The study finds 17 companies have zakat disclosure in their financial reporting for the period of study. The number of zakat paying companies keeps on increasing from 9 companies (for the year 2009) to 16 companies (for the year 2014). This study discovers the compliance rate for zakat payment among PLCs is 14%. Thus, comprehensive strategies need to be carried out especially by zakat institutions and other pertinent parties in pursuance of maximizing zakat potential especially by business entities.